Genotypes of the Cacoecia Podana Sc. Larvae in the Aes-1 Esterase Locus Differ in Their Food Micro-Niches - Andriy Simchuk (Vasyl Stefanyk Precarpathian National University, 2020)
Intergenotypic differentiation of trophic niche was studied in the system "apricot (Prunus armeniaca L.) - Cacoecia podana Sc.". C. podana larvae, carried alternative Aes-1 genotypes, were found to prefer host plant leaves, differing by length and stiffness, in their diets. Trophic micro-niches for each genotype coincided with the whole population niche in width, but differed by their optimums. There data are discussed in respect to the herbivore food specialization and population dynamics.